Hysterectomy and Bilateral Salpingoovariectomy in a Transsexual Subject without Visible Scaring. (5th July 2010) - Perrone, Anna Myriam; Scifo, Maria Cristina; Martelli, Valentina; Casadio, Paolo; Morselli, Paolo Giovanni; Pelusi, Giuseppe; Meriggiola, Maria Cristina
Abstract : Objective . To report on the use of laparoendoscopic single-site surgery (LESS) for the management of total hysterectomy (TH) with bilateral salpingoovariectomy (BSO) in a subject affected by gender identity disorder. Design . Case report. Setting . University Hospital. Patient(s) . A 27-year-old affected by Gender Identity Disorder underwent a hysterectomy and BSO as part of surgical sex reassignment. Intervention(s) . Laparoendoscopic single-site surgery access for TH and BSO. Main Outcome Measure(s) . The procedure was performed without incident. The trocar placement was easy and safe, without inadvertent port removal. No vascular or visceral injuries, loss of pneumoperitoneum, or intraoperative port site bleeding occurred. Result(s) . A detailed description of the technique of a single-site surgery for management of hysterectomy and BSO. Conclusion . Our case presents the first report of single-site surgery for surgical treatment of subjects affected by GID.